IMPLEMENTASI KEBIJAKAN PELAYANAN SOSIAL LANSIA DI PANTI PELAYANAN SOSIAL LANJUT USIA (PPSLU) KECAMATAN CEPIRING KABUPATEN KENDAL - Aisyah Khoirunnisa; Augustin Rina Herawati (Journal of Management and Public Policy, 2026)
This study aims to analyze the implementation of social service policies for the elderly at the Social Service Center for the Elderly (PPSLU) in Cepiring District, Kendal Regency, and identify the driving and inhibiting factors. The aging population phenomenon demands effective services for vulnerable elderly people, particularly in Kendal Regency, where the achievement of Minimum Service Standards (SPM) for health remains below 80%. This study employed a descriptive qualitative method, with data collection techniques including in-depth interviews, observation, and documentation studies. The analysis was conducted using George C. Edward III's theory, which encompasses the dimensions of communication, resources, disposition, and bureaucratic structure. The results indicate that the procedural implementation of social services has been carried out in accordance with SOPs and SPMs. The main driving factors are effective communication and the disposition of highly committed staff. However, the policy's success is hampered by resource limitations, particularly a minimal budget, which has resulted in damaged infrastructure and a shortage of medical personnel. Furthermore, the bureaucratic structure, with its rigid hierarchical coordination flow and building layout constraints, presents physical barriers to service delivery.